A Reportagem na tv: Caco Barcellos: um repórter e a injustiça social - Plaça Júnior, João (2004)
The present paper proposes to highlight the importance of the investigative report and show the worth that must be observed in the commitment of a TV reporter s ethical professional performance, capable of changing the course of Brazil recent political history. The practical of the authentic journalism turns out to be converting. That is what happens with the performance of the reporter Caco Barcellos. He proposed himself to chase a single story for more than a year and, in the end, disclose the truth hidden during 30 years by the public authority. Such report triggered the reparation of a social injustice done against a brazilian young student. The strength of a report presented in a TV news is undeniable, mainly because of the penetration power of TV in all social layers as news media. Its importance rises significantly considering the fact that the report was presented in a series of three consecutive days on Jornal Nacional and because this program is the leader in audience in Rede Globo. The investment of this broadcasting station in a report like the one presented in this paper depends fundamentally by the presence of a reporter profoundly identified with the fight against social injustice. This is the profile of Caco Barcellos. He grew up in a poor outskirts of a big city and since very young, he revolted himself against the police attitude, that discriminate the common citizen and privileges the powerful ones. He transformed this accumulated angry into effective actions through revealing investigative report of social injustice committed every day. In moments when the space was short for the size of the report he wanted to broadcast, Caco published books and gained prizes but also faced lawsuits, moved by policemen who intended to destroy Caco s professional life, a reporter who dared to work seriously and find the documents that proved the abuses practiced against innocents, brutally murdered. The result is a exemplary professional performance, with a work method worthy to be followed, reflecting in the series of reports that dismantled the fake created by the Army and that can be considered a true journalism lesson.